ANALYSIS OF EFFECTIVE USE OF CODE POTENTIAL AND DEPENDENCE ON ASSESSMENT METHODS - Begmatova, Ziyoda (Educational Research in Universal Sciences, 2023)
This article examines the practical tasks, factors, and economic success of effective personnel management, as well as the need to analyze personnel potential and apply applicable methods. It is designed to realize work potential, develop personal abilities, provide people with satisfaction from work done and public recognition of their achievements, and provide a comfortable environment. Personnel planning is also aimed at meeting the needs of production and ensuring the interests of employees and society as a whole. Today, more than ever, it is necessary to look for opportunities to harmonize market conditions and the interests of the company’s employee.